The importance of critical soft factors for quality improvement and organizational performance - Abdullah, Muhammad Madi; Uli, Jegak; Juan, Jose Tari (2009)
The aim of this paper is, firstly, to examine the relationships between the soft factors, quality improvement and organisational performance and secondly, advanced the study by examining quality improvement as an organisational development practice in mediating the relationship between soft factors and organisational performance in 255 Malaysia's electrical and electronics (E&E) firms. Structural equation modelling statistical technique was used to test the theoretical model. The findings showed that the quality improvement variable did mediate the relationships between all the six soft factors and organisational performance in the sampled E&E firms. Findings also highlight the relationship between soft factors, quality improvement and organisational performance.